2017
DOI: 10.1002/jsfa.8282
|View full text |Cite
|
Sign up to set email alerts
|

Integrating straw yield and quality into multi‐dimensional improvement of lentil (Lens culinaris)

Abstract: The possibility to simultaneously improve grain yield and nutritive traits of lentil straw. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
5
2
0
Order By: Relevance
“…Breeders can improve straw quality by targeting to increase CP and IVOMD or decrease NDF. Similar results were reported by Alkhtib et al (2017) in lentil and Wamatu et al (2017) in field pea. However, a simpler method is still required.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Breeders can improve straw quality by targeting to increase CP and IVOMD or decrease NDF. Similar results were reported by Alkhtib et al (2017) in lentil and Wamatu et al (2017) in field pea. However, a simpler method is still required.…”
Section: Discussionsupporting
confidence: 90%
“…Studies to simultaneously boost grain yield and straw nutritive value traits of cereal and grain legume crops are ongoing at ICARDA. Several studies have reported on the possibility of improving grain yield alongside straw traits of lentil (Alkhtib et al, 2017), chickpea (Wamatu et al, 2017), maize (Ertiro et al, 2013) and pearl millet (Blümmel et al, 2010). A focus on dual purpose hulless barley for high grain yield, high straw yield and high nutritive value would be particularly relevant for regions in Asia and Sub-Saharan Africa where straw feeding to livestock is commonly practiced.…”
Section: Introductionmentioning
confidence: 99%
“…The grain yield of the improved varieties was significantly greater than that of the local variety in this study. Similar results were reported for other leguminous crops such as faba bean [31] and lentil [35]. The local variety demonstrated inferior PUI compared to the improved varieties.…”
Section: Discussionsupporting
confidence: 84%
“…Significant varietal variations in the chemical attributes of the whole stover are consistent with the results of previous studies on common vetch (Fortina et al, 2015;Larbi et al, 2011), as well as chickpea (Kafilzadeh & Maleki, 2012), faba bean (Alkhtib et al, 2016) and cowpea (Vigna unguiculata L.; Alkhtib, Wamatu, Ejeta, & Rischkowsky, 2017). This finding also confirms that varietal differences have an effect on the biosynthesis of the CP and fibre component.…”
Section: Stover Quality Characteristicssupporting
confidence: 90%